Ijtihad as a legislative function: Role of Ijtihad, Ifta and Taqleed in Legislative Process - Shehzadi Pakeeza; Fariha Fatima (Journal of Islamic and Religious Studies, 2016)
In Islamic legislation Ijtihad plays an important role and has central position in the whole process. Demands of life change day by day thus it become necessary to take on the structural review of Islamic laws keeping in mind the spirit and discipline of Islamic. Ijtihad thus play as a perfect tool for legislation. Regarding fatawas the jurists followed the methodologies of companions, tabieen, and taba Tabaeen. In cases in which they did not find any legal opinion of their teachers related to a specific problem they themselves tried to find out the solution for that problem from the relevant Texts and formulate their own fatawa. In Pakistan the Judiciary that performs the task of interpretation for law-making, Majlis-e-Shura and various Ulama are exercising the job of Ifta. The Council of Islamic Ideology is the official legislative body of fatawa. Taqleed is also an acceptable mode of legislation whose proofs are evident from Quran and Sunnah. It has been used as a source of legislation in Pakistan as well. In constitution of Pakistan article 189 and 201 are related to Taqlid. Article 189 and 201 makes the decisions of Supreme Court binding on all courts and the High court judgments binding on all subordinate courts. Thus the legislative process in Islam employs the methods of Ijtihad, Ifta and Taqlid as a perfect tool of legislation.